2009
DOI: 10.1007/s00441-009-0757-2
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of reticular framework of white pulp and marginal zone in human spleen: immunohistochemical studies of fetal spleens from the 17th to 40th week of gestation

Abstract: The antigenic heterogeneity of the reticular framework of the white pulp (WP) and marginal zone (MZ) is well documented in the human adult spleen. The ontogeny of the WP and MZ of human fetal spleens was examined with special reference to the heterogeneity of the reticular framework. In the spleen of the 17th gestational week (gw), alpha-smooth muscle actin (alpha-SMA)-positive reticulum cells were scattered around the arterioles. From the 20th to 23rd gw, alpha-SMA-positive reticulum cells increased in number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In embryonic spleen, Nkx2-5cre + mesenchymal cells were shown to express transcripts for Ltbr, Cxcl13, and Vcam1, and upon transplantation to develop into functional FRCs and FDCs organizing T and B zones, respectively (Castagnaro et al, 2013). In fetal human spleen, the organization and growth of an aSMA + reticular cell network was found to be associated with B cell accumulation and WP growth and organization (Satoh et al, 2009;Steiniger et al, 2007). Our flow cytometric analysis, cell sorting, and histological analysis of LTbR-expressing cells from neonatal spleen identified the chemokine-expressing LTo as being a mesenchymal cell type expressing not only LTbR but also PDGFRa/b, desmin, and Ccl19-cre.…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic spleen, Nkx2-5cre + mesenchymal cells were shown to express transcripts for Ltbr, Cxcl13, and Vcam1, and upon transplantation to develop into functional FRCs and FDCs organizing T and B zones, respectively (Castagnaro et al, 2013). In fetal human spleen, the organization and growth of an aSMA + reticular cell network was found to be associated with B cell accumulation and WP growth and organization (Satoh et al, 2009;Steiniger et al, 2007). Our flow cytometric analysis, cell sorting, and histological analysis of LTbR-expressing cells from neonatal spleen identified the chemokine-expressing LTo as being a mesenchymal cell type expressing not only LTbR but also PDGFRa/b, desmin, and Ccl19-cre.…”
Section: Discussionmentioning
confidence: 99%
“…In human and rat spleen, a-SMAcontaining reticular cells were also demonstrated in the PALS; but in follicles, these cells were rare, corresponding to sparse reticulum cells and reticulin fibers in this area. FDCs may replace a-SMA-positive reticular cells in germinal centers (Toccanier-Pelte et al 1987;Satoh et al 1997Satoh et al ,2009Steiniger et al 2001). In vivo imaging has shown that the FDC network displays a marked mobility, and FDCs in culture express a-SMA (Bajénoff et al 2006;Muñoz-Fernández et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The reticular network must permit great volume changes during an immune response, e.g., associated with the development and regression of germinal centers (Veerman and Vries 1976;Liu et al 1991;Hollowood and Macartney 1992). Accordingly, contractile proteins characteristic of smooth muscle are expressed by reticular cells (Pinkus et al 1986;Toccanier-Pelte et al 1987;Satoh et al 1997Satoh et al ,2009Steiniger et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…PALS, follicles and marginal zone develop in the mid gestational period and towards the end of this trimester the red and white pulp are clearly distinguishable[46][47][48][49].3.2.2.1.2. Postnatal.…”
mentioning
confidence: 99%